Windspharm: A high-level library for global wind field computations using spherical harmonics - Dawson, A (Software Sustainability Institute, 2016)
The windspharm library is a Python package for performing computations on global wind fields in spherical geometry. It provides a high-level interface for computing derivatives and integrals of vector wind fields over a sphere using spherical harmonics. The software allows for computations with plain arrays, or with structures that include metadata, integrating with several popular data analysis libraries from the atmospheric and climate science community. The software is available on Github.